2011
DOI: 10.1111/j.1399-0012.2011.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil monotherapy in liver transplant recipients

Abstract: In summary, our data support the safety and efficacy of CNI to MMF monotherapy conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Mycophenolic acid (MPA) was selected for its ability to inhibit de novo synthesis of purine and was consequently developed into the morpholinoethyl ester of MPA under the name MMF 68 . MMF has high bioavailability and is hydrolyzed to MPA after oral administration to prevent T- and B-cell proliferation by inhibiting inosine monophosphate dehydrogenase, which controls de novo biosynthesis of purine 68 , 69 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycophenolic acid (MPA) was selected for its ability to inhibit de novo synthesis of purine and was consequently developed into the morpholinoethyl ester of MPA under the name MMF 68 . MMF has high bioavailability and is hydrolyzed to MPA after oral administration to prevent T- and B-cell proliferation by inhibiting inosine monophosphate dehydrogenase, which controls de novo biosynthesis of purine 68 , 69 .…”
Section: Resultsmentioning
confidence: 99%
“…In renal transplant studies, MMF showed effectiveness in acute rejection rescue therapy, and combination administration of cyclosporine and MMF significantly reduced acute allograft rejection compared to placebo or azathioprine, another antagonist of purine metabolism 68 . In liver transplant studies, conversion from CNI to MMF monotherapy led to significant improvements in the serum creatinine level and calculated GFR 69 . Based on the most recent retrospective study of MMF monotherapy enrolling 94 liver transplant patients, the regimen was feasible without a high risk of acute rejection (4.2%, 4/94), and the estimated GFR was significantly increased by 6.3% for up to 5 years 71 .…”
Section: Resultsmentioning
confidence: 99%
“…Most patients are off corticosteroids by 3 months after LT. 109 Patients on dual therapy and have stable graft function may be switched to TAC monotherapy any time after 3 months. 59,110,111 TAC minimization with EVR or MMF is done in patients with renal dysfunction. Complete withdrawal of TAC with EVR or MMF monotherapy increases the risk of rejection, and it is not recommended in the first year after transplantation.…”
Section: Immunosuppression Minimization Protocolsmentioning
confidence: 99%